Operating conditions influence on VMD and SGMD for ethanol recovery from aqueous solutions - Muvdi Nova, Carlos Jesús; Barón Núñez, Fredy Wsvaldo; Cotamo De la Espriella, Ricardo Javier (CT&F - Ciencia, Tecnología y Futuro, 2015)
This work focuses on Vacuum Membrane Distillation (VMD) and Sweeping Gas Membrane Distillation (SGMD) as a separating technique of ethanol from aqueous solutions. VMD was studied at moderate temperature (30, 40 and 50°C) and pressure (0.11, 0.20 and 0.30 atm) conditions, whereas SGMD was studied at different temperatures (50 and 70°C) and air-flow rates (10x10-6 and 20x10-6 m3.min-1). These techniques were experimentally studied using prepared ethanol-water solutions and fermented broths, with ethanol at 10% w/w. Under these operating conditions and using prepared ethanol-water solutions, an average total flux of 22.61 and 1.6 kg.m-2.h-1, and concentration factors of 2.3 and 1.7 were obtained for VMD and SGMD, respectively. For fermented broths, total flux of 17.66 and 0.9 kg.m-2.h-1, and concentration factors of 1.8 and 1.9 were obtained for VMD and SGMD, respectively. The fouling impact was also studied, finding a significant effect of pressure (vacuum) for VMD technique; mainly due to the biomass presence in the solution. Experimental results show that applying pressurization/depressurization cycles decreases membrane fouling, stabilizing flux and concentration in the permeate. While for SGMD configuration, the incidence of fouling was significantly lower.